Fungsi dan Jenis Tindak Tutur Komunikasi Panitia Pembangunan Musala Arroudloh Dusun Belut Desa Ngumpul Kecamatan Jogoroto Kabupaten Jombang - Moh. Zainudin; Eka Nurjanah; Yolandha Yulia Elizabeth (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
This study aims to describe the function and types of speech acts of communication of the Musala Arroudloh development committee, Belut Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency. This research design is descriptive-qualitative. The subject of this research is the Musala Arroudloh development committee, Belut hamlet, Ngumpul Village, Jogoroto District, Jombang Regency. The object of research is the function and types of speech acts that were uttered by the development committee of Musala Arroudloh Belut Hamlet, Ngumpul Village, Jogoroto District, Jombang Regency. Data collection techniques include observation, interviews, and documentation. Data analysis carried out by researchers are: (1) data reduction. This activity includes selecting data on the basis of its level of relevance and relation to data groups, compiling data in similar units, and creating codes. (2) displaying data by compiling relevant data, (3) drawing conclusions to get a meaning of scattered symptoms to have deep meaning. The results of this study indicate that: (1) the function of the speech act of the Musala Arroudloh development committee, includes the assertive function, directive function, commissive function, and expressive function. (2) types of speech acts of the Musala Arroudloh development committee, namely direct lateral speech acts and lateral indirect speech acts. The function of assertive and directive speech acts is a function that often appears in communication opportunities between the Musala Arroudloh development committee, while the type of direct lateral speech act is the type of speech act that is widely used in communication opportunities between committees because there is no difference between speech and meaning and delivery intent. Keywords: the speech of the Arroudloh Musala development committee, functions and types of speech acts